An under-diagnosed cause of leg swelling. (24th May 2013) - Goodliffe, James M; Ormerod, Julian O M; Beale, Andrew; Ramcharitar, Steve
Abstract : A grossly obese woman was wrongly diagnosed throughout her adult life of having lymphoedema. Her condition was subsequently confirmed as lipoedema, an entirely different condition, which is noted in medical text books but is seldom taught to medical students or to general practitioners. The condition is caused by abnormal deposition of adipose tissue in the extremities (usually the lower limbs) and almost exclusively affects women. It often starts at puberty or may occur after pregnancy. The exact aetiology is not yet understood but genetic and hormonal factors may be implicated. The problem is that misdiagnosis leads to inappropriate tests and improper treatment to the patient. When recognised it is often too late to do anything for the patient and they become highly dependent on social care. This case describes how the diagnosis can be confirmed through an ultrasound image and illustrates the need for early recognition to facilitate specialist care.